Performance Analysis of ZigBee Mesh WSN in Carbon Monoxide Gas Monitoring System - Muhammad Fuad; Muhammad Iqbal; Mamat Rahmat; Heru Sukoco; Husin Alatas (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The need for air pollutant monitoring system is very substantial especially in the developing countries such as Indonesia. In this research, we have performed a test of such system for carbon monoxide gas based on wireless sensor network (WSN) using ZigBee. This system is working with a mesh topology where each sensor node can communicate with one another. There are seven nodes that serve as sensor nodes and one node serving as Coordinator. Each sensor node has five components that represent of gas sensors. We measure three performance metrics during the test, i.e. throughput, delay, and packet loss. The system has been successfully implemented which is capable of displaying information in real time. The experiment resulted in an average carbon monoxide value of 25.1 ppm and showed a good performance. It showed a throughput more than 1.017 kbps, delay and packet loss ratio less than 409 ms and 5 %, respectively.